SOME MORPHOLOGICAL CHARACTERISTICS OF TURKISH TAZI (SIGHT HOUND) - O. Yılmaz; M. Ertuğrul (Journal of Animal and Plant Sciences, 2011)
This study was carried out to determine the distributions of body coat colour and the body measurements of the Turkish Tazi (Sighthound) comparing with some other sight hound breeds from different countries. To this end, a data of 122 (60 male and 62 female) Tazi were analyzed with the Minitab 15 statistical software program using ANOVA and Student’s t-Test. Descriptive statistics for live weight (LW) 18.4 ± 0.19, withers height (WH) 62 ± 0.35, height at rump (HR) 62.2 ± 0.35, body length (BL) 60.3 ± 0.39, heart girth circumference (HGC) 63.3 ± 0.42, chest depth (CD) 22.8 ± 0.27, abdomen depth (AD) 14.3 ± 0.14, chest width (CW) 17.3 ± .0.16, haunch width (HW) 16.2 ± 0.12, thigh width (TW) 21.9 ± 0.17, tail length (TL) 44.8 ± 0.37, limb length (LL) 39.2 ± 0.20, cannon circumference (CC) 10.2 ± 0.07, head length (HL) 23.7 ± 0.21 and ear length (EL) 12.3 ± 0.13 cm respectively. In this study the distributions of body coat color of the sampled Tazi, as percentages, for black was 35.2%, dun 25.4%, brown 12.3%, tan 10.7%, white 8.2% and pied 8.2% respectively.
Keywords: Turkish Tazi; sighthound; morphological trait; body measurement; coat colour.